Lithium-rich manganese-based positive electrode material subjected to hydrothermal auxiliary post-treatment as well as preparation method and application of lithium-rich manganese-based positive electrode material
The surface modification of lithium-rich manganese-based oxide powder is solved by hydrothermal-assisted post-treatment method, which solves the problem of capacity decay and voltage decay during the circulation process, and achieves higher Coulomb efficiency and cycling stability.
Patent Information
- Application Number
- CN202411838229.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
The lithium-rich manganese-based positive electrode material has a large irreversible capacity loss during the first charging and discharging process, and the specific capacity of the cyclic discharge gradually declines, and the voltage attenuates significantly during circulation, which affects its commercialization process.
The surface modification of lithium-rich manganese-based oxide powder is used to use polyethylene glycol to improve the surface structure and stability of the material through hydrothermal reaction and subsequent sintering steps.
The first Coulomb efficiency and discharge specific capacity of lithium-rich manganese-based cathode material is significantly improved, its cycle stability and rate performance are enhanced, and the energy consumption of the preparation process and the processing complexity of the material are reduced.
Smart Images

Figure CN119660825A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a hydrothermal-assisted post-processed lithium-manganese-based positive electrode material and a preparation method and application thereof. Background Art
[0002] The chemical formula of lithium-rich manganese-based cathode materials can be expressed as Li 1+x M 1-x O2 (where M = Mn, Co and Ni, x>0) has a higher proportion of lithium content and can release a high discharge capacity (250 mAh g) under high voltage conditions. -1 ), and the Ni and Co contents are low, which is conducive to cost reduction. These advantages meet the development requirements of lithium-ion batteries in terms of cost and endurance, so lithium-rich manganese-based positive electrode materials can be used as the next generation positive electrode of lithium-ion batteries.
[0003] However, lithium-rich manganese-based positive electrode materials have large irreversible capacity losses during the first charge and discharge process, the specific capacity of the cycle discharge gradually declines, and the voltage decays significantly during the cycle, which has become an important factor hindering its commercialization process. During the electrochemical reaction, the surface of the electrode material is the site of the electrochemical reaction, and its surface properties directly affect the performance and stability of the electrode material. In order to improve the performance of the electrode material, the existing technology realizes the surface modification of the electrode material through post-treatment, such as the application of (NH4)2SO4, HNO3 or other acidic reagents for treatment, which can achieve the modification of most of the surface particles more uniformly, thereby improving the first coulombic efficiency and cycle performance of the lithium-rich manganese-based positive electrode material. This method reduces costs while achieving good technical effects. However, the surface modification of electrode materials using acidic reagents such as HNO3 can enhance the wettability of the materials in the electrolyte by introducing oxygen-containing or nitrogen-containing functional groups and change the pore structure and surface structure of the materials. Although this can improve certain electrochemical properties, such as initial discharge capacity and high-rate performance, it may also affect the structural stability of the materials and be detrimental to the cycle stability. At the same time, the introduction of protons may also cause the electrolyte solution to produce more HF in the battery reaction. In addition, acidic reagents are also corrosive and toxic, which may pose risks to the environment and the health of operators during use.
[0004] Therefore, how to design effective, reliable and safe strategies to improve the various performances of lithium-rich manganese-based oxide materials through material surface modification is a technical problem that technicians in this field urgently need to solve. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a hydrothermal-assisted post-processed lithium-manganese-based positive electrode material and a preparation method and application thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A method for preparing a lithium-rich manganese-based positive electrode material comprises: using polyethylene glycol to perform surface modification on lithium-rich manganese-based oxide powder by a hydrothermal-assisted post-treatment method to obtain the lithium-rich manganese-based positive electrode material.
[0009] Furthermore, the preparation method of the lithium-rich manganese-based positive electrode material comprises the following steps:
[0010] The lithium-rich manganese-based oxide powder is dispersed in a mixed solution of polyethylene glycol and water, and a hydrothermal reaction is performed to obtain a post-processed powder. The post-processed powder is then washed, dried and sintered to obtain the lithium-rich manganese-based positive electrode material.
[0011] Furthermore, the lithium-rich manganese-based oxide powder is Li 1.2 Mn 0.54 Ni 0.33 Co 0.33 O2; the polyethylene glycol is polyethylene glycol-300.
[0012] The lithium-rich manganese-based oxide in the present invention is a spherical material particle assembled by primary particles, has a larger size and a smaller specific surface area, and often exhibits a lower first coulombic efficiency and discharge specific capacity. The hydrothermal reaction process can roughen the material surface, further improving the reaction efficiency.
[0013] Furthermore, the material-liquid ratio of the lithium-rich manganese-based oxide powder to polyethylene glycol is 0.5 g: (2-16) mL.
[0014] Furthermore, the material-liquid ratio of the lithium-rich manganese-based oxide powder to polyethylene glycol and water is 0.5 g: (2-16) mL: (2-16) mL.
[0015] The above ratio of water and polyethylene glycol helps the lithium-rich manganese-based oxide powder to form a moderate surface roughness, making it easier for lithium ions to escape, thereby avoiding problems such as low material capacity and rapid capacity decay.
[0016] Furthermore, the temperature of the hydrothermal reaction is 200° C. and the time is 3 hours.
[0017] Furthermore, the particle size of the lithium-rich manganese-based oxide powder is 10-15 μm.
[0018] Furthermore, the drying temperature is 80° C. and the drying time is 4 hours; and / or
[0019] The sintering temperature is 400° C. and the sintering time is 1 hour.
[0020] The lithium-rich manganese-based oxide of the present invention can obtain an activated and stable surface structure by being treated with a mixed solution containing polyethylene glycol and water under hydrothermal conditions and subsequently sintered at high temperature.
[0021] The polyethylene glycol used in the preparation process of the lithium-rich manganese-based positive electrode material of the present invention is miscible with water to form a uniform mixed solution, which can fully infiltrate the lithium-rich manganese-based oxide powder material, so that the lithium-rich manganese-based oxide powder particles are acted on both the inside and outside under hydrothermal conditions. During the hydrothermal-assisted post-treatment process of the lithium-rich manganese-based oxide powder, the residual alkali components on the surface are removed, and at the same time, the polyethylene glycol and the material undergo redox reactions to reconstruct the surface structure of the material, which is beneficial to the insertion and removal of lithium ions (the (003) peak at about 19° in the XRD spectrum of the treated lithium-rich manganese-based material shifts toward the low 2θ value direction, that is, the c value of the layered structure becomes larger, which is beneficial to the insertion and removal of lithium ions). In addition, the subsequent 400°C sintering process can remove residual polyethylene glycol or other by-products, thereby stabilizing the lithium-rich manganese-based material. Therefore, the hydrothermal-assisted post-treatment process of the present invention can activate the lithium-rich manganese-based oxide material, so that it has a better first coulomb efficiency and discharge specific capacity.
[0022] The second technical solution of the present invention:
[0023] A lithium-rich manganese-based positive electrode material is prepared according to the above preparation method.
[0024] The surface of the lithium-rich manganese-based positive electrode material prepared by the above preparation method of the present invention is roughened, and has obvious differences in surface properties from the original positive electrode material. After cyclic charge and discharge, the first coulombic efficiency and discharge specific capacity of the material are significantly improved.
[0025] The third technical solution of the present invention:
[0026] Application of the lithium-rich manganese-based positive electrode material in lithium-ion batteries.
[0027] Furthermore, the lithium-ion battery is a button battery.
[0028] The fourth technical solution of the present invention:
[0029] A lithium-ion battery comprises a lithium sheet negative electrode, an electrolyte, a polypropylene-based microporous diaphragm and a composite positive electrode, wherein the composite positive electrode comprises the lithium-rich manganese-based positive electrode material described in the above technical solution.
[0030] Furthermore, the composite positive electrode is prepared by coating a mixture of the lithium-rich manganese-based positive electrode material, conductive carbon black (Super P carbon black) and polyvinylidene fluoride binder on aluminum foil.
[0031] Furthermore, the mass ratio of the lithium-rich manganese-based positive electrode material, the conductive carbon black and the polyvinylidene fluoride binder is 8:1:1.
[0032] Furthermore, the electrolyte is LiPF6 / EC-EMC-DMC.
[0033] Compared with the prior art, the present invention has the following advantages and technical effects:
[0034] The present invention can effectively solve the technical problems of rate performance and rate difference of lithium-rich manganese-based oxides. The preparation method of lithium-rich manganese-based positive electrode materials is simple. The polyethylene glycol material used in the preparation process is easy to obtain and low in cost. The preparation process only requires hydrothermal treatment at 200°C and sintering at 400°C in a short time. The energy consumption of the preparation process is low, and the material processing process is simple and easy to reproduce. The lithium-rich manganese-based positive electrode material prepared by the present invention can effectively improve the specific capacity, first coulomb efficiency and ultra-high cycle stability of lithium-ion batteries, and also shows excellent rate discharge performance, and has broad commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0036] Figure 1 XRD patterns of lithium-rich manganese-based cathode materials prepared in Example 1 and scanning electron microscope images (SEM) at different magnifications, wherein (a) is an XRD comparison diagram of different samples between 18 and 20° and 65 and 68°, and (b) and (c) are high-magnification and low-magnification scanning diagrams, respectively;
[0037] Figure 2 The charge and discharge performance of the lithium ion battery (hydrothermal-assisted post-treatment sample) of Example 1 and the lithium ion battery (untreated sample) of Comparative Example 1 at different rates, wherein (a) is the first charge and discharge curve of the untreated and hydrothermal-assisted post-treatment samples at a current density of 100 mA / g, and (b) is the cycle performance diagram of the untreated and hydrothermal-assisted post-treatment samples at a current density of 100 mA / g;
[0038] Figure 3 The charge and discharge performance results of the lithium ion battery of Example 1 at different rates;
[0039] Figure 4 The charge and discharge performance results of the lithium-ion battery of Example 2 at different rates. DETAILED DESCRIPTION
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0041] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] The embodiment of the present invention provides a method for preparing a lithium-rich manganese-based positive electrode material, wherein a lithium-rich manganese-based oxide powder is surface-modified using polyethylene glycol by a hydrothermal-assisted post-treatment method to obtain the lithium-rich manganese-based positive electrode material, and the method specifically comprises the following steps:
[0046] The lithium-rich manganese-based oxide powder is dispersed in a mixed solution of polyethylene glycol and water, and a hydrothermal reaction is performed to obtain a post-processed powder. The post-processed powder is then washed, dried and sintered to obtain the lithium-rich manganese-based positive electrode material.
[0047] In a preferred embodiment of the present invention, the lithium-rich manganese-based oxide powder is Li 1.2 Mn 0.54 Ni 0.33 Co 0.33O2; the polyethylene glycol is polyethylene glycol-300; illustratively, the lithium-rich manganese-based oxide powder Li used in the embodiment of the present invention 1.2 Mn 0.54 Ni 0.33 Co 0.33 The method for preparing O2 is:
[0048] (1) MnSO4, NiSO4 and CoSO4 were weighed according to the molar ratio of Mn:Ni:Co=0.54:0.33:0.33, and then dissolved in distilled water until the solution was completely dissolved to obtain a solution A with a transition metal ion concentration of 1 mol / L. A mixed solution B of ammonia water, ammonium sulfate and potassium carbonate with concentrations of 0.1 mol / L, 0.1 mol / L and 1 mol / L were also prepared;
[0049] (2) In a reaction kettle at 60° C., the mixed solution B is slowly added to the continuously stirred solution A, and the pH value of the process is controlled to be 8;
[0050] (3) After precipitation is complete, continue stirring for 6 h, and then filter and dry the precipitate;
[0051] (4) 1.8 g of the obtained precipitate was mixed with 3% excess of lithium hydroxide monohydrate and ground, and then transferred into a high-temperature furnace and sintered at 500° C. for 4 h, and then heated to 900° C. and continued to sinter for 12 h to obtain lithium-rich manganese-based oxide powder Li 1.2 Mn 0.54 Ni 0.33 Co 0.33 O2.
[0052] In a preferred embodiment of the present invention, the material-liquid ratio of the lithium-rich manganese-based oxide powder to polyethylene glycol and water is 0.5 g: (2-16) mL: (2-16) mL.
[0053] In a preferred embodiment of the present invention, the temperature of the hydrothermal reaction is 200° C. and the time is 3 hours.
[0054] In a preferred embodiment of the present invention, the particle size of the lithium-rich manganese-based oxide powder is 10-15 μm.
[0055] In a preferred embodiment of the present invention, the drying temperature is 80° C. and the drying time is 4 hours.
[0056] In a preferred embodiment of the present invention, the sintering temperature is 400° C. and the sintering time is 1 hour.
[0057] The embodiment of the present invention further provides a lithium-rich manganese-based positive electrode material, which is prepared according to the above preparation method.
[0058] The embodiment of the present invention also proposes the application of the lithium-rich manganese-based positive electrode material in a lithium-ion battery.
[0059] Exemplarily, the lithium-ion battery is a lithium-ion button battery, which includes a lithium sheet negative electrode, an electrolyte, a polypropylene-based microporous separator and a composite positive electrode, and the composite positive electrode includes the lithium-rich manganese-based positive electrode material.
[0060] In a preferred embodiment of the present invention, the composite positive electrode is prepared by coating a mixture of the lithium-rich manganese-based positive electrode material, conductive carbon black (Super P carbon black) and polyvinylidene fluoride binder on aluminum foil, wherein the mass ratio of the lithium-rich manganese-based positive electrode material, conductive carbon black and polyvinylidene fluoride binder is 8:1:1.
[0061] In a preferred embodiment of the present invention, the electrolyte used is LiPF6 / EC-EMC-DMC.
[0062] The Super P carbon black used in the embodiments of the present invention was purchased from Shenzhen Kejing Company, the polyvinylidene fluoride binder was purchased from Aldrich Reagent Company, and the electrolyte LiPF6 / EC-EMC-DMC used was purchased from Kelude Company. The concentration of lithium salt LiPF6 in the electrolyte was 1 mol / L, and the solvent was a mixture of diethyl carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a mass ratio of 1:1:1.
[0063] In the embodiments of the present invention, normal temperature refers to "25±2°C".
[0064] The technical solution of the present invention is further illustrated by the following embodiments.
[0065] Example 1
[0066] A method for preparing a lithium-rich manganese-based positive electrode material comprises the following steps:
[0067] 0.5 g lithium-rich manganese-based oxide powder (Li 1.2 Mn 0.54 Ni 0.33 Co 0.33 O2, particle size of 10-15 μm) was dispersed in a mixed solution of 2 mL polyethylene glycol-300 and 16 mL distilled water, and then transferred to a 40 mL polytetrafluoroethylene reactor, and the reactor was placed in an oven for hydrothermal reaction at 200 ° C for 3 hours. After the reaction, the powder in the reactor was washed with distilled water and placed in an oven at 80 ° C for 4 hours. After drying, it was sintered in a high-temperature furnace at 400 ° C for 1 hour to obtain an oxide powder, which is a lithium-rich manganese-based positive electrode material.
[0068] Comparative Example 1
[0069] The raw material lithium-rich manganese-based oxide powder of Example 1 is directly used as the positive electrode material.
[0070] The XRD pattern of the lithium-rich manganese-based positive electrode material prepared in Example 1 of the present invention and the scanning electron microscope (SEM) images at different magnifications are shown in Figure 1 , where (a) is the XRD comparison diagram of different samples between 18 and 20° and 65 and 68°, (b) and (c) are high-magnification and low-magnification scanning diagrams, respectively. It can be seen that the particle surface of the sample has been roughened, and the high-resolution transmission structural analysis shows the presence of spinel.
[0071] A lithium-ion button battery comprises a lithium sheet negative electrode, an electrolyte, a polypropylene-based microporous diaphragm and a composite positive electrode, wherein the composite positive electrode is prepared by coating a mixture of the lithium-rich manganese-based positive electrode material prepared in Example 1 or the lithium-rich manganese-based oxide powder in Comparative Example 1, conductive carbon black (Super P carbon black) and polyvinylidene fluoride binder on an aluminum foil, wherein the mass ratio of the lithium-rich manganese-based positive electrode material, the conductive carbon black and the polyvinylidene fluoride binder is 8:1:1.
[0072] After the lithium-ion button cells were assembled in a glove box under argon protection conditions with water and oxygen values below 1 ppm, they were tested using Shenzhen Neware battery testing system.
[0073] The battery test system tests the charge and discharge performance of the lithium ion battery of Example 1 (hydrothermal assisted post-treatment sample) and the lithium ion battery of Comparative Example 1 (untreated sample) at different rates. Figure 2 , wherein (a) is the first charge and discharge curve of the untreated and hydrothermal assisted post-treatment samples at a current density of 100 mA / g, (b) is the cycle performance diagram of the untreated and hydrothermal assisted post-treatment samples at a current density of 100 mA / g, wherein the charge and discharge performance results of the lithium ion battery of Example 1 at different rates are shown in Figure 3It can be seen that the button-type lithium-ion battery assembled using the lithium-rich manganese-based positive electrode material prepared in Example 1 of the present invention as the positive electrode of the lithium-ion battery has a high first coulombic efficiency, cycle stability and excellent rate performance compared to the untreated material. The lithium-ion battery finally obtained has a first discharge specific capacity of 203.14 mAh / g and a first coulombic efficiency of 72% at a current density of 100 mA / g, and a 100-cycle capacity retention rate of 90.2%; and at a current density of 200 mA / g, the specific capacity can reach 185.12mAh / g, and the capacity retention rate of 100 cycles can reach 88.1%; when the current density is 400mA / g, the discharge specific capacity of the first cycle and 100 cycles can reach 161.9mAh / g and 149.6mAh / g, and the capacity retention rate can reach 92.4%; when the current density is 1000mA / g, the discharge specific capacity of the first cycle and 100 cycles is 152.6mAh / g and 140.0mAh / g, respectively, and the capacity retention rate can reach 91.7%. Compared with the untreated sample, the lithium-rich manganese-based positive electrode material prepared by the method of Example 1 of the present invention significantly improves the first coulomb efficiency, discharge specific capacity and rate performance.
[0074] Example 2
[0075] A method for preparing a lithium-rich manganese-based positive electrode material comprises the following steps:
[0076] 0.5 g lithium-rich manganese-based oxide powder (Li 1.2 Mn 0.54 Ni 0.33 Co 0.33 O2, particle size of 10-15 μm) was dispersed in a mixed solution of 6 mL polyethylene glycol-300 and 12 mL distilled water, and then transferred to a 40 mL polytetrafluoroethylene reactor, and the reactor was placed in an oven for hydrothermal reaction at 200 ° C for 3 hours. After the reaction, the powder in the reactor was washed with distilled water and placed in an oven at 80 ° C for 4 hours. After drying, it was sintered in a high-temperature furnace at 400 ° C for 1 hour to obtain an oxide powder, which is a lithium-rich manganese-based positive electrode material.
[0077] A lithium ion button battery comprises a lithium sheet negative electrode, an electrolyte, a polypropylene-based microporous diaphragm and a composite positive electrode, wherein the composite positive electrode is prepared by coating a mixture of the lithium-rich manganese-based positive electrode material prepared in Example 2, conductive carbon black (Super P carbon black) and a polyvinylidene fluoride binder on an aluminum foil, wherein the mass ratio of the lithium-rich manganese-based positive electrode material, the conductive carbon black and the polyvinylidene fluoride binder is 8:1:1.
[0078] After the lithium-ion button cells were assembled in a glove box under argon protection conditions with water and oxygen values below 1 ppm, they were tested using Shenzhen Neware battery testing system.
[0079] The battery test system tests the charge and discharge performance of the lithium-ion battery of Example 2 at different rates. Figure 4 . It can be seen that the lithium-ion battery assembled using the lithium-rich manganese-based positive electrode material prepared in Example 2 of the present invention has a maximum discharge specific capacity of 165 mAh / g at a current density of 100 mA / g, and a 100-cycle retention rate of 84%. The maximum discharge specific capacity at a current density of 200 mA / g is 145 mAh / g, and a 100-cycle retention rate of 80%. The maximum discharge specific capacity at a current density of 400 mA / g is 135.3 mAh / g, and a 100-cycle retention rate of 80.1%. The maximum discharge specific capacity at a current density of 1000 mA / g is 102 mAh / g, and a 100-cycle retention rate of 67%.
[0080] Example 3
[0081] A method for preparing a lithium-rich manganese-based positive electrode material comprises the following steps:
[0082] 0.5 g lithium-rich manganese-based oxide powder (Li 1.2 Mn 0.54 Ni 0.33 Co 0.33 O2, particle size of 10-15 μm) was dispersed in a mixed solution of 9 mL polyethylene glycol-300 and 9 mL distilled water, and then transferred to a 40 mL polytetrafluoroethylene reactor, and the reactor was placed in an oven for hydrothermal reaction at 200°C for 3 hours. After the reaction, the powder in the reactor was washed with distilled water and placed in an oven at 80°C for 4 hours. After drying, the oxide powder was sintered in a high-temperature furnace at 400°C for 1 hour to obtain a lithium-rich manganese-based positive electrode material.
[0083] A lithium ion button battery comprises a lithium sheet negative electrode, an electrolyte, a polypropylene-based microporous diaphragm and a composite positive electrode, wherein the composite positive electrode is prepared by coating a mixture of the lithium-rich manganese-based positive electrode material prepared in Example 3, conductive carbon black (Super P carbon black) and a polyvinylidene fluoride binder on an aluminum foil, wherein the mass ratio of the lithium-rich manganese-based positive electrode material, the conductive carbon black and the polyvinylidene fluoride binder is 8:1:1.
[0084] After the lithium-ion button cells were assembled in a glove box under argon protection conditions with water and oxygen values below 1 ppm, they were tested using Shenzhen Neware battery testing system.
[0085] After testing by a battery testing system, the discharge performance results of a lithium-ion battery assembled using the lithium-rich manganese-based positive electrode material prepared in Example 3 of the present invention at different rates showed that the maximum discharge specific capacity of the lithium-ion battery at current densities of 100mA / g, 200mA / g, 400mA / g and 1000mA / g were 144mAh / g, 137mAh / g, 120mAh / g and 101mAh / g, respectively, and the 100-cycle retention rates were 90%, 95%, 92% and 81%, respectively.
[0086] Example 4
[0087] A method for preparing a lithium-rich manganese-based positive electrode material comprises the following steps:
[0088] 0.5 g lithium-rich manganese-based oxide powder (Li 1.2 Mn 0.54 Ni 0.33 Co 0.33 O2, particle size of 10-15 μm) was dispersed in a mixed solution of 16 mL polyethylene glycol-300 and 2 mL distilled water, and then transferred to a 40 mL polytetrafluoroethylene reactor, and the reactor was placed in an oven for hydrothermal reaction at 200 ° C for 3 hours. After the reaction, the powder in the reactor was washed with distilled water and placed in an oven at 80 ° C for 4 hours. After drying, the oxide powder was sintered in a high-temperature furnace at 400 ° C for 1 hour to obtain a lithium-rich manganese-based positive electrode material.
[0089] A lithium ion button battery comprises a lithium sheet negative electrode, an electrolyte, a polypropylene-based microporous diaphragm and a composite positive electrode, wherein the composite positive electrode is prepared by coating a mixture of the lithium-rich manganese-based positive electrode material prepared in Example 4, conductive carbon black (Super P carbon black) and a polyvinylidene fluoride binder on an aluminum foil, wherein the mass ratio of the lithium-rich manganese-based positive electrode material, the conductive carbon black and the polyvinylidene fluoride binder is 8:1:1.
[0090] After the lithium-ion button cells were assembled in a glove box under argon protection conditions with water and oxygen values below 1 ppm, they were tested using Shenzhen Neware battery testing system.
[0091] After testing by a battery testing system, the discharge performance results of a lithium-ion battery assembled using the lithium-rich manganese-based positive electrode material prepared in Example 4 of the present invention at different rates showed that the maximum discharge specific capacity of the lithium-ion battery at current densities of 100mA / g, 200mA / g, and 400mA / g were 100mAh / g, 81mAh / g, and 68mAh / g, respectively, and the 100-cycle retention rates were 95%, 82%, and 90%, respectively.
[0092] Comparative Example 2
[0093] The same as Example 1, except that the reactor was placed in an oven at 100° C. for 3 hours of hydrothermal reaction.
[0094] After battery performance testing (testing method is the same as that of Example 1), the lithium-ion battery composed of the comparative sample has a discharge capacity of 163.5 mAh / g and 130.6 mAh / g at a current density of 100 mA / g for the first cycle and 100 cycles, respectively. Compared with the sample of Example 1, the initial capacity, cycle performance and 100-cycle discharge capacity of the sample of Comparative Example 2 are all poor, because the reaction process between the material and polyethylene glycol cannot be formed under the condition of 100°C, which is equivalent to the water washing step of the conventional positive electrode material.
[0095] Comparative Example 3
[0096] The same as Example 1, except that the sintering step is omitted, specifically:
[0097] 0.5 g lithium-rich manganese-based oxide powder (Li 1.2 Mn 0.54 Ni 0.33 Co 0.33 O2, particle size of 10-15 μm) was dispersed in a mixed solution of 2 mL polyethylene glycol-300 and 16 mL distilled water, and then transferred to a 40 mL polytetrafluoroethylene reactor. The reactor was placed in an oven for a hydrothermal reaction at 200 ° C for 3 hours. After the reaction, the powder in the reactor was washed with distilled water and placed in an oven at 80 ° C for 4 hours to obtain a lithium-rich manganese-based positive electrode material.
[0098] After battery performance testing (testing method is the same as that of Example 1), the lithium ion battery composed of the comparative sample has a discharge capacity of 191.5 mAh / g and 169.6 mAh / g at a current density of 100 mA / g for the first cycle and 100 cycles, respectively. The electrochemical performance of the comparative sample is lower than that of the sample in Example 1, which may be due to the unstable surface structure of the sample that loses some oxygen and lithium elements after the reaction.
[0099] Comparative Example 4
[0100] The same as Example 1, except that the step of adding polyethylene glycol-300 is omitted, specifically:
[0101] 0.5 g lithium-rich manganese-based oxide powder (Li 1.2 Mn 0.54 Ni 0.33 Co 0.33O2, particle size of 10-15 μm) was dispersed in 18 mL of distilled water, and then transferred to a 40 mL polytetrafluoroethylene reactor. The reactor was placed in an oven at 200°C for a hydrothermal reaction for 3 hours. After the reaction, the powder in the reactor was washed with distilled water and placed in an oven at 80°C for 4 hours. After drying, the oxide powder was sintered in a high-temperature furnace at 400°C for 1 hour to obtain a lithium-rich manganese-based positive electrode material.
[0102] After battery performance test (test method is the same as that of Example 1), the lithium ion battery composed of the comparative sample has a discharge capacity of 172.4 mAh / g and 146.8 mAh / g at a current density of 100 mA / g for the first cycle and 100 cycles, respectively. Compared with Example 1, the electrochemical performance of the comparative sample is poor, and the reason is that there is no reaction process between the raw material and polyethylene glycol for modification, which is equivalent to the water washing step of the conventional positive electrode material and only removes the unstable components on the surface of the raw material, such as residual alkali or lithium carbonate after reaction with air.
[0103] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a lithium-rich manganese-based positive electrode material, characterized in that: The lithium-rich manganese-based positive electrode material is obtained by using polyethylene glycol to modify the surface of the lithium-rich manganese-based oxide powder using a hydrothermal assisted post-treatment method.
2. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The following steps are involved: The lithium-rich manganese-based oxide powder is dispersed in a mixed solution of polyethylene glycol and water, and a hydrothermal reaction is performed to obtain a post-processed powder. The post-processed powder is then washed, dried and sintered to obtain the lithium-rich manganese-based positive electrode material.
3. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The material-liquid ratio of the lithium-rich manganese-based oxide powder to polyethylene glycol is 0.5 g: (2-16) mL.
4. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 200° C. and the time is 3 hours.
5. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The particle size of the lithium-rich manganese-based oxide powder is 10-15 μm.
6. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The drying temperature is 80°C and the drying time is 4 hours; and / or The sintering temperature is 400° C. and the sintering time is 1 hour.
7. A lithium-rich manganese-based positive electrode material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.
8. Use of the lithium-rich manganese-based positive electrode material as claimed in claim 7 in lithium-ion batteries.
9. A lithium ion battery comprising a lithium sheet negative electrode, an electrolyte, a polypropylene-based microporous diaphragm and a composite positive electrode, characterized in that: The composite positive electrode comprises the lithium-rich manganese-based positive electrode material according to claim 7.
10. The lithium ion battery according to claim 9, characterized in that: The composite positive electrode is prepared by coating a mixture of the lithium-rich manganese-based positive electrode material according to claim 7, conductive carbon black and polyvinylidene fluoride binder on aluminum foil.